Introduction: Thinking Places: Indigenous Humanities and Education - Battiste, Marie; McConaghy, Cathryn (The Australian Journal of Indigenous Education, 2005)
Every conception of humanity arises from a specific place and from the people of that place. How such places shape and sustain the people of a place is the focus of education that enables each student to understand themselves and makes them feel at home in the world. The notion of Indigenous humanities being developed at the University of Saskatchewan in Saskatoon represents an example of such ecological teachings and practices of what constitutes humanity. Ecology is the animating force that teaches us how to be human in ways that theological, moral and political ideologies are unable to. Ecology privileges no particular people or way of life. It does, however, promote Indigenous humanity as affirmed in Article 1 of the 1966 UNESCO Declaration of the Principles of International Cultural Co-operation: “Each culture has a dignity and value which must be respected and preserved” (Office of the High Commissioner for Human Rights, 1966). In the Eurocentric versions of humanity, this concept is sometimes referred to as cultural diversity; yet Indigenous peoples prefer the concept of Indigenous humanities.